(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
– A number of problems affecting productivity can be noted when the activities in progress on a typical construction site are closely observed. Productivity improvements give higher cost savings with minimal investment. Lean construction is relatively a new construction management philosophy which has evolved from Lean Manufacturing principles. Lean construction along with its various tools like Pull Approach, Just in Time (JIT), The Last Planner System (LPS), Total Quality Management (TQM), Work Sampling (WS)and Value Stream Mapping (VSM) etc. has gathered a lot of momentum in the developed nations. The challenge now lies in implementing it in the developing countries. The main purpose of Lean construction is efficiency improvement by elimination of non-value adding activities (Waste). The aim of the project is to implement the Lean construction tools in an ongoing construction project at Rahatani, Pune to identify wastes in construction activities and improve the process flow by eliminating wasteful activities.